Daily intake of wheat germ-enriched bread may promote a healthy gut bacterial microbiota: a randomised controlled trial - Moreira-Rosário, André (2020)
Wheat bran fibre has a beneficial effect on gastrointestinal function, but evidence for wheat germ is scarce. Accordingly, we evaluated the effects of daily intake of wheat germ on gastrointestinal discomfort and gut microbiota by adding wheat germ to refined (white) wheat bread, the most consumed bread type. We hypothesised that an improvement in the composition of refined bread could beneficially affect intestinal health without compromising consumers' acceptance.